Die Ressortverteilung als Instrument zur Enthaftung der GmbH-Geschäftsführung - Mascherini, Giancarlo (Studien zum Gesellschaftsrecht, 2021)
Managing directors are increasingly burdened with obligations. If this tendency persists, they must be given the possibility to share these responsibilities among them. Only if they are allowed to distribute the numerous liability risks inherent to their duties they are able to focus on the tasks they are best qualified for. The present study addresses this need de lege lata applying the corporate law principles of management organisation. It develops precise and practical criteria on how to allocate portfolios to effectively limit the managing directors' liability without, however, compromising the legitimate interests of creditors. The research not only targets academics, but is intended to be a vademecum for legal and company practice.